Interdisciplinary and practical approaches to managerial education and training - Pardal, Pedro; Teixeira, Nuno Miguel; Carvalho, Luísa Cagica (IGI Global, 2022)
"This book addresses the main topics of interest regarding the best practices, laboratory methods, policies, protocols, in the areas of business education and managerial training offering topics related to practical approaches to managerial education and training